Menos complementares e redundantes, porém mais jovens: organização de assembleias de aves em monoculturas florestais - Labecca, Fábio Martins (2015)
The increasing demand for timber and pulpwood has triggered an increase in areas of tree monocultures. The effects of native vegetation conversion in such monocultures have been extensively debated, but the consequences of this land use change to functionality and evolutionary history conservation have been little studied. Here, we evaluated how the avifauna responds to nature ecosystem conversion in tree monocultures by quantifying changes in local diversity (alpha diversity) and in assemblage composition (beta diversity), in their functional and phylogenetic components. We compiled forty paired bird lists in native vegetation areas and in comparable tree monoculture areas. Changes in alpha diversity were quantified by paired tests of observed values in native vegetation and in tree monocultures, and changes in assemblages composition through additive partitioning of beta diversity in nestedness and turnover components. We observed that tree monocultures are impoverished in number of species, supporting lower functional richness and less functionally similar assemblages. This demonstrates that environmental filter selecting and limiting similarity processes concurrently modify functional structure of bird assemblages, resulting in loss of functional complementarity and redundancy. Species in tree monocultures are also evolutionary younger and less related to each other. We showed that bird assemblages in tree monoculture are composed largely by functionally and phylogenetic different species from that assemblages in native vegetation. Body size, diet and foraging traits were the major functional traits in predicting the absence of the species in tree monocultures. Alson, we show that annual average temperature, annual average pluviosity and stage of understory development in tree monocultures are important predictors of diversity loss in these type of monoculture.